Design Of Cash Accounting Information Systems Of Cash In Aa Bogor Electrical Shop: Design Of Cash Accounting Information Systems Of Cash In Aa Bogor Electrical Shop - Priatno Priatno; Adinda Yunita Nur Ibrahim; Muhamad Ryansyah (Institute of Computer Science (IOCS), 2020)
The development of information technology is now growing rapidly and rapidly. The use of computers is very much needed in almost every company. Computers and systems are very helpful to improve the performance and profit of a company. In processing sales data, AA Electric Stores still use manual notes using paper media and calculators. So that errors often occur in calculations. And the reports produced are only stored in the form of documents as archives. While these documents are very important for the company. For this reason, the author made the Final Project regarding the sales system at AA Electric Stores which until now has not been computerized. This information system design is the best solution to solve the problems that exist in this company, making it easier for users to make sales transactions, so that there is no error in the calculation and processing of neatly arranged goods data. The process of running sales transactions and processing data of goods becomes more effective and efficient. Data can be stored safely and easily searched, And with this system makes it easier for the owner to view the report at any time because when the data entered into the system will be processed directly into report information. And to improve the company's performance, it is necessary to design a purchasing system at the AA Electric Store. A web-based sales and purchase system is designed for company performance more effectively.